Der Mensch im Tod nach der "Apokalypse des Mose " Eine frühjüdische Anthropologie in der Zeit des Paulus - Schreiber, Stefan 1967- (2004)
In the Apocalypse of Moses the themes of the protoplasts’ death and of God’s mercy with Adam are dominant. The anthropological views, how- ever, are ambivalent: man as a unity, or a dichotomy of body and soul. In the literary setting of the document as a whole, traditio-historical solutions are not satisfying. On the background of the use of the key terms soma, pneuma, and psyche in the Septuagint, the author of the Apocalypse does not provide a clear anthropological system, but articulates the “self,” the “life” of man as owed to God. Avoiding the dualistic picture of man common in Greek philosophy, he is guided by the biblical view of man as a unity in order to strengthen the reader’s hope in a life after death in the face of negative earthly conditions. This has consequences, for example, for the theological diversity in Early Judaism, or for the dilemma of the empty tomb of Jesus.